A Reproductive Threat-Based Model of Evolved Sex Differences in Jealousy - Brad J. Sagarin; D. Vaughn Becker; Rosanna E. Guadagno; Wayne W. Wilkinson; Lionel D. Nicastle (Evolutionary Psychology, 2012)
Although heterosexual women and men consistently demonstrate sex differences in jealousy, these differences disappear among lesbians and gay men as well as among heterosexual women and men contemplating same-sex infidelities (infidelities in which the partner and rival are the same sex). Synthesizing these past findings, the present paper offers a reproductive threat-based model of evolved sex differences in jealousy that predicts that the sexes will differ only when the jealous perceivers' reproductive outcomes are differentially at risk. This model is supported by data from a web-based study in which lesbians, gay men, bisexual women and men, and heterosexual women and men responded to a hypothetical infidelity scenario with the sex of the rival randomly determined. After reading the scenario, participants indicated which type of infidelity (sexual versus emotional) would cause greater distress. Consistent with predictions, heterosexual women and men showed a sex difference when contemplating opposite-sex infidelities but not when contemplating same-sex infidelities, whereas lesbians and gay men showed no sex difference regardless of whether the infidelity was opposite-sex or same-sex.